TÜRKİYE'DE YETİŞEN BAZI ONOBRYCHİS MİLLER (FABACEAE) TÜRLERİ ÜZERİNDE SİTOTAKSONOMİK BİR ARAŞTIRMA - SEPET, HAKAN (Fırat Üniveristesi, 2007)
Bu çalısmada, Türkiye genelinde yayılıs gösteren Onobrychis Miller cinsine ait 8 tür (O.caputgalli (L) LAM O.aequidentata (Sibth. & Sm.) d'Urv, O. fallax Freyn & Sint. var. fallax, O. lasiostachya Boiss, O. viciifolia Scop., O .oxyodonta Boiss. subsp. armena (Bois. & Huet) Aktoklu , O.hypargyrea Boiss., O. cappadocica Boiss.), karyolojik ve sitotaksonomik bakımdan incelenmistir. 0ncelenen türler, Lophobrychis, Onobrychis ve Hymenobrychis seksiyonlarında yer almaktadır. 0ncelenen 8 türün (O. caput-galli. O. aequidentata, O.fallax, O. lasiostachya, O. viciifolia, O. armena, O. hypargyrea, O. cappadocica) kromozom çalısmaları için tohumlarından yararlanılmıstır. Kromozom çalısmaları sonucunda türlerin somatik kromozomlarının sayım ve ölçümleri yapılmıstır. Sekiz türden O.cappadocica 2n=16, O.viciifolia 2n=28, digerleri 2n=14 bulunmustur. Bütün kromozomlar median noktalı (M), median bölgeli (m) ve submedian (sm) sentromerli bulundu. Anahtar Kelimeler: Onobrychis, Fabaceae, Kromozom sayısı, sitotaksonomi, Karyotip

In this study, Eight species belong to genus Onobrychis Miller in growing Turkey (O.caput-galli (L) LAM O.aequidentata (Sibth. & Sm.) d' Urv, O. fallax Freyn & Sint. var. fallax, O. lasiostachya Boiss, O. viciifolia Scop., O .oxyodonta Boiss. subsp. armena (Bois. & Huet) Aktoklu , O.hypargyrea Boiss., O. cappadocica Boiss.) were investigated in point of karyologic and cytotaxonomic. Investigated species were placed in Lophobrychis, Onobrychis and Hymenobrychis sections. The seeds of investigated eight species (O. caput-galli. O. aequidentata, O.fallax, O. lasiostachya, O. viciifolia, O. armena, O. hypargyrea, O. cappadocica) were used for chromosomes analysis. The numbers and measurements of somatic chromosomes were carried in results of chromosomes works. In this species, the chromosome numbers were in O cappadocica and 2n=16 in O vicifolia 2n=28 and 2n= 14 in other species. All of the chromosomes had median point (M), median region (m), or submedian (sm) centromeres. Key words: Onobrychis, , Fabaceae, Chromosome numbers, Cytotaxonomy, Karyotype
A cytotaxonomic investigation on some Onobrychis species growing in Turkey
Keywords: Botanik; Biyoloji